-8p=42-42p

Simple and best practice solution for -8p=42-42p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8p=42-42p equation:


Simplifying
-8p = 42 + -42p

Solving
-8p = 42 + -42p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '42p' to each side of the equation.
-8p + 42p = 42 + -42p + 42p

Combine like terms: -8p + 42p = 34p
34p = 42 + -42p + 42p

Combine like terms: -42p + 42p = 0
34p = 42 + 0
34p = 42

Divide each side by '34'.
p = 1.235294118

Simplifying
p = 1.235294118

See similar equations:

| x^2+3x=45 | | 5x+4=39 | | x^2+3x=45x | | 3x^6+6x^5-9x^4+6x^3=0 | | 5x+4=41 | | 8x+10=12x-90 | | 24x-50=4x-20 | | 9(4x+1)= | | -7a+50=-6-7(6+3a) | | 20x+30=10x+90 | | x^3+14x^2+49x=0 | | 2x+51.5=4x+3 | | 8(1-p)=-24-4p | | x^3-15=0 | | y=0.2192x+15.29 | | 100+14r= | | 0.2192x+15.29= | | 2x+4/3+54= | | R=100 | | 5(4x-6)-3x=47+6x | | 2+8+9+6-87-654-9+87654= | | 0.2187x+15.67= | | -2(4s-1)-2=-2(6s+7)-3 | | -(6z+2)(2-8z)+(-7z-6)(2-2z)= | | 3y=12-y | | 2x+20=70 | | x^2+15x+11=2x-1 | | 5.6-.32x=1.12 | | x^2+10x+18=9 | | 140-2x=34x+20 | | y=0.2187x+15.67 | | 3sinx+cosx=2 |

Equations solver categories